Cognitive Domain Assessment Instrument in Learning at SMA Muhammadiyah 5 Yogyakarta - Rahman, M. Faqih Syifa; Hidayah, Nurul; Swadi, Swadi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study aims to examine the application of test techniques as an assessment instrument for the cognitive domain in learning at SMA Muhammadiyah 5 Yogyakarta. The background of this research is the importance of assessments that are able to measure the ability to think at a higher level according to the demands of 21st century education. The method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. Data analysis is carried out using the Miles and Huberman model, which includes data reduction, data presentation, and verification. The results showed that teachers used a combination of objective tests (such as multiple choice) and essay tests to assess students' abilities from low to high cognitive levels based on the revised Bloom Taxonomy. Tests are used not only to assess learning outcomes, but also to provide feedback and improve the learning process. The main challenges faced by teachers include difficulties in compiling HOTS questions, time constraints, and high workloads. To overcome this, schools apply strategies such as question preparation training, collaboration between teachers, and the use of digital technology in the evaluation process. This study concludes that the application of planned test techniques and in accordance with the principles of authentic assessment can increase the effectiveness of cognitive assessment, learning quality, and students' critical thinking skills in the modern education era.